Desenvolvimento de matriz de quitosana/PVA, quimicamente reticulado para aplicação potencial em engenharia de tecido epitelial - Ezequiel de Souza Costa Junior (2008)
The skin is the organ of corporal covering that exercises the function of body boundary, between the body and the environment, therefore have functions as interface body/environment. That role requires both specific and much complex transition functions of the organ, and is subject to various kinds of demands and wounds provoked by agents from different sources, such as, electromagnetic, chemical, mechanical, physical, etc. and the countless combinations between them. However the skin presents a capacity of considerable self-repairing. Those characteristics of the skin have prompted countless researches in order to reveal the phenomena that occur in this tissue and to find materials that facilitate and accelerate the self-repairing process. The increasing demand for synthetic materials to be used in tissue repair also results from the limited sources of autogenous graft biomaterials and from the increased risk for the health, associated to alogenous grafts. This work was carried out aiming at the preparation and characterization, from the mechanical, chemical and physical standpoint, the degradation in vitro and the cellular viability in vitro of hybrid biomaterial based on polymers from both synthetic and natural sources, chitosan/poly(vinyl alcohol-co-vinyl acetate), chemically crosslinked with glutaraldehyde, and to build a three-dimensional matrix to be used as a degradable epithelial tissue substitute. The investigated system provided encouraging results regarding its application in vivo. The mechanical properties, swelling behavior, degradation rate in vitro and cellular viability were compatible with the characteristic of an epithelial tissue. The material presented a toughness range from 1.4 to 34MJ/m3, swelling from 150% to 700% in 24h, degradation rate range of 20% and 75% in 24h and cellular viability in vitro above 60% compared to the cellular control.